2007
DOI: 10.1128/cvi.00055-06
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Administration Early in Life Impairs Specific Humoral Responses to an Oral Antigen and Increases Intestinal Mast Cell Numbers and Mediator Concentrations

Abstract: In this study, we assessed the effect of administering the antibiotic amoxicillin to rat pups on the immune response to orally fed ovalbumin (OVA). We first established that amoxicillin administration durably altered the gut microbiota of these animals. In parallel, we observed that the induction of the specific humoral response to ovalbumin was impaired when it occurred during antibiotic administration to the rat pups. We also examined the consequences of those observations on further allergic reactions. Amox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 49 publications
(45 reference statements)
1
6
0
1
Order By: Relevance
“…They were fed the rest of their daily feed allowance without supplemental antibiotic afterwards. The amoxicillin dosage used here was intermediate between values found in the literature for pigs (20 mg/kg BW/day [21] ) and rats (100 mg/kg BW/day [22] ). Amoxicillin was distributed from 10 days before the estimated farrowing date till 21 days after farrowing.…”
Section: Methodsmentioning
confidence: 53%
“…They were fed the rest of their daily feed allowance without supplemental antibiotic afterwards. The amoxicillin dosage used here was intermediate between values found in the literature for pigs (20 mg/kg BW/day [21] ) and rats (100 mg/kg BW/day [22] ). Amoxicillin was distributed from 10 days before the estimated farrowing date till 21 days after farrowing.…”
Section: Methodsmentioning
confidence: 53%
“…However, the absence of immunosuppression in the after-7-days-of-medication group clearly indicated that the drug was completely excreted and did not interact with immune cells to modulate the immune response. The results are concomitant with the similar structurally related drug, amoxycillin, which impaired antibody titre in rat pups immunized with oval albumin (18). In addition, researchers also categorize ampicillin as an immunodepressing antibiotic (19).…”
Section: Effect Of Ampicillin On Igg Antibody Titrementioning
confidence: 79%
“…These studies have determined a relationship between oral tolerance and GIT microbial composition in both adult and infant mice. The mechanisms mediated by the flora for oral tolerance induction are not yet clear, but are probably mediated by shifts in TLR signaling, Th1/Th2 balance, and/or due to alterations of antigen presenting cells in the intestinal tract [38] , [39] , [40] . Recently the response of adult mice to influenza infection of the respiratory tract following 4 weeks of antibiotic treatment was interrogated [41] .…”
Section: Discussionmentioning
confidence: 99%